2015
DOI: 10.1002/ccd.25867
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative acute kidney injury on clinical outcomes after transcatheter aortic valve implantation: A meta‐analysis of 5,971 patients

Abstract: Postoperative AKI seems to significantly worsen TAVI prognosis. The results of the present meta-analysis should be considered hypothesis-generating and future studies on risk stratification, prevention, and postoperative management are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 40 publications
4
65
1
4
Order By: Relevance
“…PARTNER, PARTNER 2A, and SURTAVI trials showed a marked lower rate of AKI in TAVR compared to SAVR at 30-day follow-up (1.3 vs. 3.1, P=0.006; 6 vs. 15.1, P<0.001 and 1.7 vs. 4.4, 95% CI: −4.4 to −1.0 respectively) that was maintained at 1 and 2-year follow-up (13,14,19). A metaanalysis confirmed the importance of AKI on survival, showing that patients with AKI have a 5-fold increase in 30-day mortality and 3-fold increase at 1-year post TAVR (51). In a propensity score analysis with SAVR, TAVR with Sapien 3 in intermediate risk patients showed 6-fold reduction in AKI (0.5% vs. 3.3%), a similar rate of major vascular complications (6.1% vs. 5.4%) and a strong difference in life-threatening/ disabling bleeding (4.6 vs. 46.7) and cardiac death (0.9% vs. 3.1%) (52).…”
Section: Bleeding and Acute Kidney Injury (Aki)supporting
confidence: 52%
“…PARTNER, PARTNER 2A, and SURTAVI trials showed a marked lower rate of AKI in TAVR compared to SAVR at 30-day follow-up (1.3 vs. 3.1, P=0.006; 6 vs. 15.1, P<0.001 and 1.7 vs. 4.4, 95% CI: −4.4 to −1.0 respectively) that was maintained at 1 and 2-year follow-up (13,14,19). A metaanalysis confirmed the importance of AKI on survival, showing that patients with AKI have a 5-fold increase in 30-day mortality and 3-fold increase at 1-year post TAVR (51). In a propensity score analysis with SAVR, TAVR with Sapien 3 in intermediate risk patients showed 6-fold reduction in AKI (0.5% vs. 3.3%), a similar rate of major vascular complications (6.1% vs. 5.4%) and a strong difference in life-threatening/ disabling bleeding (4.6 vs. 46.7) and cardiac death (0.9% vs. 3.1%) (52).…”
Section: Bleeding and Acute Kidney Injury (Aki)supporting
confidence: 52%
“…AKI remains a common complication immediately after transcatheter aortic valve implantation (TAVI), however, its detection varied considerably depending on the definition used . This complication is likely the combination of contrast‐induced nephrotoxicity (CIN), microembolization of atherosclerotic plaque debris due to delivery of large devices in the aorta, and/or hypotension in an individual with abnormal baseline renal function/reserve .…”
mentioning
confidence: 99%
“…Acute kidney injury should be promptly diagnosed and treated, nephrotoxic drugs should be stopped, and patients whom will benefit from renal replacement therapy should be identified. 22 The usefulness of renal protection devices (e.g., Renal guard; RenalGuard Solutions, Inc., Milford, Massachusetts) is currently at most uncertain. 23 Female gender has been found to be a positive predictor for survival in some TAVI cohorts and neutral in others.…”
Section: Discussionmentioning
confidence: 99%